Monoclonal Antibodies Targeting Surface-Exposed and Secreted Proteins from Staphylococci - Pietro Speziale; Giampiero Pietrocola (Vaccines, 2021)
Staphylococci (specifically Staphylococcus aureus and Staphylococcus epidermidis) are the causative agents of diseases ranging from superficial skin and soft tissue infections to severe conditions such as fatal pneumonia, bacteremia, sepsis and endocarditis. The widespread and indiscriminate use of antibiotics has led to serious problems of resistance to staphylococcal disease and has generated a renewed interest in alternative therapeutic agents such as vaccines and antibodies. Staphylococci express a large repertoire of surface and secreted virulence factors, which provide mechanisms (adhesion, invasion and biofilm development among others) for both bacterial survival in the host and evasion from innate and adaptive immunity. Consequently, the development of antibodies that target specific antigens would provide an effective protective strategy against staphylococcal infections. In this review, we report an update on efforts to develop anti-staphylococci monoclonal antibodies (and their derivatives: minibodies, antibody–antibiotic conjugates) and the mechanism by which such antibodies can help fight infections. We also provide an overview of mAbs used in clinical trials and highlight their therapeutic potential in various infectious contexts.